Kontribusi Ulama Tajwid terhadap Perkembangan Ilmu Bahasa - Al Rasyid, Harun (SUHUF, 2009)
This paper exposes some great works ofÃ‚Â  tajweed scholar to the phonetic studies in Arabic language. The QurÃ¢â‚¬â„¢anic scholars and their studies of tajweed knowledge (the rules of reciting QurÃ¢â‚¬â„¢an) have given a significant contribution to the correct pronunciation in sounding the ArabicÃ‚Â  fonemsÃ‚Â  (hurfÃ‚Â  hijÃ„ÂÃ¢â‚¬â„¢iyyah). Furthermore, other significant contribution is to give full attention to the beauty of the sound on reading Al-QurÃ¢â‚¬â„¢an.